Genetic Diversity and Transmission of Multidrug-Resistant Mycobacterium tuberculosis strains in Lusaka, Zambia - Joseph Yamweka Chizimu (Elsevier, 2022)
ABSTRACT: Objective: Zambia is among the 30 high tuberculosis burden countries in the world. Despite increasing reports of multidrug-resistant tuberculosis (MDR-TB) in routine surveillance, information on the transmission of MDR Mycobacterium tuberculosis strains is largely unknown. This study elucidated the genetic diversity and transmission of MDR M. tuberculosis strains in Lusaka, Zambia. Methods: Eighty-five MDR M. tuberculosis samples collected from 2013 to 2017 at the University Teaching Hospital were used. Drug-resistance associated gene sequencing, spoligotyping, 24-loci mycobacterial interspersed repetitive units-variable number of tandem repeats (MIRU-VNTR), and multiplex PCR for RD-Rio sub-lineage identification were applied. Results: The identified clades were LAM (48%), CAS (29%), T (14%), X (6%) and Harlem (2%). Strains belonging to SITs 21/CAS1-Kili and 20/LAM1 formed the largest clonal complexes. Combined spoligotyping and 24 loci-MIRU-VNTR revealed 47 genotypic patterns with a clustering rate of 63%. Ninety-five percent of LAM strains belonged to the RD-Rio sub-lineage. Conclusion: The high clustering rate suggested that a large proportion of MDR-TB was due to recent transmission rather than the independent acquisition of MDR. This spread was attributed to clonal expansion of SIT21/CAS1-Kili and SIT20/LAM1 strains. Therefore, TB control programs recommending genotyping coupled with conventional epidemiological methods can guide measures for stopping the spread of MDR-TB.